1984
DOI: 10.1007/bf00436195
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of the fission yeast Schizosaccharomyces pombe

Abstract: The Schizosaccharomyces pombe strain EF1 (CBS 356) is haploid, prototrophic, respiratory competent, and of homothallic mating type. From restriction enzyme analysis the length of the mitochondrial genome is 17.3 kilobase pairs, which is in good agreement with the value of 17.1 kilobase pairs determined by electron microscopy. The mitochondrial genome of strain EF1 is thus about 2.3 kilobase pairs shorter than that of strain ade7-50h- (about 19.4 kilobase pairs). A restriction map was constructed for 11 enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The reference S. pombe mitogenome (accession numbers NC_001326.1 and X54421.1) was from a Leupold-background strain with the genotype h − ade7-50 (Lang 1984; Zimmer et al. 1984).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference S. pombe mitogenome (accession numbers NC_001326.1 and X54421.1) was from a Leupold-background strain with the genotype h − ade7-50 (Lang 1984; Zimmer et al. 1984).…”
Section: Resultsmentioning
confidence: 99%
“…No complete mitogenome sequences of any other S. pombe isolates have been reported thus far. Restriction fragment analysis and limited Sanger sequencing have indicated that presence–absence polymorphisms of mitochondrial introns are widespread among S. pombe isolates (Zimmer et al. 1984, 1987), but an accurate and thorough understanding of intraspecific mitogenomic variation of S. pombe is still lacking.…”
Section: Introductionmentioning
confidence: 99%